EMPOWERING UNDERPRIVILEGED FAMILIES THROUGH THE DEVELOPMENT OF A CRACKERS VILLAGE IN SIRNASARI VILLAGE - Ummu Salamah, Imas; Panji Suhenda, Dede; Selpia, Peti (Al-Mubin, 2025)
Empowering underprivileged families is a strategic effort to improve community welfare by strengthening the local economy. This study aims to develop the Kampung Kerupuk (Crackers Village) as an economic empowerment model for underprivileged families in Sirnasari Village. The methods used in this program include identifying village potential, providing training in production and business management, marketing assistance, and evaluating the economic impact on the community. The results indicate that empowerment through the cracker business has enhanced community production skills, expanded market access through digital marketing, and encouraged the formation of joint business groups. Additionally, support from stakeholders such as the village government, local SMEs, and cooperatives has contributed to the program's sustainability. With a participatory and community-based approach, the development of Kampung Kerupuk in Sirnasari Village has proven to be an effective solution for increasing the income of underprivileged families and creating a sustainable economic ecosystem